The impact of long-only index funds on price discovery and market performance in agricultural futures markets; Der Einfluss von Long-only-Indexfonds auf die Preisfindung und das Marktergebnis an landwirtschaftlichen Warenterminmärkten - Sören Prehn; Thomas Glauben; Jens-Peter Loy; Ingo Pies; Matthias Georg Will (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2014)
For a considerable time, long-only index funds have been suspected of being responsible for price increases on agricultural futures markets, particularly those for grain. Utilizing partial equilibrium concepts, we analyze the market impacts of long-only index funds. Our analysis reveals that long-only index funds stabilize the market. The market entry of long-only index funds lowers risk premiums, so farmers can hedge at lower costs. This gives incentives for storage and dampens seasonal price fluctuations on spot markets, which is also in favor of consumers. However, the entry of long-only index funds reduces the profitability of speculation. Thus, there is no need for political action in this particular field. – – Long-only-Indexfonds stehen seit geraumer Zeit unter Verdacht, für die Preisanstiege an landwirtschaftlichen Warenterminmärkten, in sbesondere für Getreide, verantwortlich zu sein. Anhand von partiellen Gleichgewichts konzepten untersuchen wir die langfristige Marktwirkung von Long-only-Indexfonds. Unsere Analyse zeigt, dass Long-only-Indexfonds den Markt stabilisieren. Der Markteintritt von Long-only-Indexfonds verringert die Risikoprämie, so dass Landwirte sich zu geringeren Kosten absichern können. Dieses fördert die Lagerhaltung und schwächt so saisonale Preisschwankungen am Kassamarkt ab, was auch im Interesse der Konsumenten ist. Allerdings wird durch den Markteintritt von Long-only-Indexfonds die Rentabilität des Spekulierens verringert. Von daher gibt es keine Notwendigkeit für politische Maßnahmen in diesem speziellen Bereich.
urn:nbn:de:gbv:3:2-28691
Keywords: G1; G13; Q02; Q14; 330; agricultural futures markets; price discovery; long-only index funds; Landwirtschaftliche Warenterminmärkte; Preisbildung; Long-only-Indexfonds